Designing a Curriculum and Learning Program for the Creative Industry’s Challenge and Workforce Development - Chotib, Mochamad Nasrul; Widodo, Herditya Wahyu; Subagyo, Kukuh Prayitno; Sujiatmoko, Ahmad Heki; Yannuar, Nurenzia; Adyatma, Adham; Q. Z., Gizka Namira; Waradani, Indira Rizqita; P., Juanita Maharani (UI Scholars Hub, 2024)
This article discusses the importance of developing a learning track to respond to the demands of the creative market industry in the community, particularly with regard to journalism and related content creation. The study is based on a collaborative workshop conducted with practitioners from the Indonesian platform Kapanlagi Youniverse. The results of this preliminary study indicate that designing a curriculum and learning program that aligns with current industry practices is essential for preparing the journalism and creative content workforce. Collaborating with industry practitioners is crucial to competing in the rapidly evolving creative industry. The findings also suggest that incorporating subjects such as focused journalism and specific writing, as well as collaborative subjects, into up-to-date learning programs is vital for meeting contemporary industry requirements. Furthermore, the study highlights the needs to take action to develop an undergraduate curriculum that leverages relevant materials, media, and artificial intelligence (AI) technologies. By preparing the creative industry’s workforce in the community, we can enhance its readiness, thus fostering a circular learning process that benefits the community as a whole.